Evil and Christian ethics - Graham, Gordon, 1949 July 15- (Cambridge, UK ; New York, NY : Cambridge University Press, 2001)
Genocide in Rwanda, multiple murder at Denver or Dunblane, the gruesome activities of serial killers - what makes these great evils, and why do they occur? In addressing such questions this book, unusually, interconnects contemporary moral philosophy with work in New Testament scholarship. The conclusions to emerge are surprising. Gordon Graham argues that the inability of modernist thought to account satisfactorily for evil and its occurrence should not lead us to embrace an eclectic postmodernism, but to take seriously some unfashionable pre-modern conceptions - Satan, demonic possession, spiritual powers, cosmic battles. Precisely because it strives to observe the high standards of clarity and rigour that are the hallmarks of philosophy in the analytical tradition, the book makes a powerful case for the rejection of humanism and naturalism, and for explaining the moral obligation to struggle against evil by reference to the New Testament's cosmic narrative.
1. Christian ethics or moral theology? -- 2. The real Jesus -- 3. Evil and action -- 4. Forces of light and forces of darkness -- 5. The transformation of evil -- 6. The theology of hope.
Includes bibliographical references (pages 230-234) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Christian ethics; Good and evil; Good and evil; Morale chrétienne.; Mal; JUVENILE NONFICTION -- General; Christian ethics; Good and evil; Übel; Christliche Ethik; Das Böse; Christelijke ethiek; Het Kwaad; Morale chrétienne.; Mal, Problème du -- Christianisme; Electronic books; Electronic books